1993
DOI: 10.1128/jb.175.10.2970-2979.1993
|View full text |Cite
|
Sign up to set email alerts
|

The murI gene of Escherichia coli is an essential gene that encodes a glutamate racemase activity

Abstract: The murI gene of Escherichia coli was recently identified on the basis of its ability to complement the only mutant requiring D-glutamic acid for growth that had been described to date: strain WM335 of E. coli B/r (P. Doublet, J. van Heijenoort, and D. Mengin-Lecreulx, J. Bacteriol. 174:5772-5779, 1992). We report experiments of insertional mutagenesis of the murI gene which demonstrate that this gene is essential for the biosynthesis of D-glutamic acid, one of the specific components of cell wall peptidoglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 43 publications
5
77
0
Order By: Relevance
“…The dga (murl) gene was identified by its ability to complement the D-glutamate auxotrophic phenotype of the only known Dglutamic-acid-requiring mutant, E. coli B/r WM335 (9,12), and could be stably maintained on high-copy-number pUC vectors (5,6). Doublet et al recently reported data that suggest that dga (murI) encodes a racemase enzyme in E. coli (4). This finding is supported by our own experimental data and protein sequence analysis.…”
supporting
confidence: 74%
“…The dga (murl) gene was identified by its ability to complement the D-glutamate auxotrophic phenotype of the only known Dglutamic-acid-requiring mutant, E. coli B/r WM335 (9,12), and could be stably maintained on high-copy-number pUC vectors (5,6). Doublet et al recently reported data that suggest that dga (murI) encodes a racemase enzyme in E. coli (4). This finding is supported by our own experimental data and protein sequence analysis.…”
supporting
confidence: 74%
“…Involvement of the gbnU gene product in peptidoglycan synthesis. Since the effects on bacterial shape and cell integrity provoked by the defect of glmU resembled the phenotypes of previously characterized mutants defective in peptidoglycan synthesis (4,8,22,23,26,33,37), the effect of a temperature upshift on peptidoglycan synthesis in both strains JM83(pGMU) and UGS83 was determined. In order to estimate the rate of synthesis of this macromolecule, we directly quantitated the cell peptidoglycan content by amino acid and amino sugar analyses of isolated sacculi.…”
Section: Resultsmentioning
confidence: 99%
“…The pGM7 plasmid (10) carrying the 4.6-kb NcoI-ClaI fragment that encompasses both the glmU and glmS genes (Fig. 2) (8).…”
Section: Resultsmentioning
confidence: 99%
“…We constructed an in-frame deletion of murI in our improved sacB-based suicide vector, pMP812. Since it has been shown that it is possible to rescue D-glutamate auxotrophs with exogenous D-glutamate in Bacillus subtilis and E. coli B/r and K-12 strains (Ashiuchi et al, 2007;Doublet et al, 1993;Hoffmann et al, 1972), we performed a standard two-step allelic exchange (LoVullo et al, 2006) using pMP884 (Table 1) with D-glutamic acid present in the medium. We then picked and patched 24 sucroseresistant secondary recombinants onto media with or without D-glutamic acid.…”
Section: Allelic Exchange Of Muri and Complementation With The Singlementioning
confidence: 99%
“…We chose to interrupt the production of D-glutamate by deleting the murI gene, which encodes a glutamate racemase that is essential to E. coli (Doublet et al, 1993). D-Glutamate is indispensable for the biosynthesis of peptidoglycan in most eubacteria, and is produced through two known routes: by D-amino acid transferase (D-AAT), which converts a-ketoglutarate to D-glutamate by transamination with D-alanine provided by the alanine racemase reaction; and by glutamate racemase, which produces Dglutamate through the racemization of L-glutamate (Liu et al, 1998).…”
Section: Allelic Exchange Of Muri and Complementation With The Singlementioning
confidence: 99%